2010
DOI: 10.1108/02580541011055634
|View full text |Cite
|
Sign up to set email alerts
|

Creating HR value through technology

Abstract: PurposeThe purpose of this paper is to investigate how human resources (HR) can create value for an organization through the use of technology.Design/methodology approachThe paper looks at areas in which HR can create value through the use of technology. It introduces the e‐HRM Value Model based on a range of themes that emerged form research interviews and an systematic review of a wide range of literature.FindingsThe e‐HRM Value Model argues that value can be created in one of three ways: HR operational cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…In comparison to traditional HRM approaches, e-HRM can help to streamline transactional HRM activities; speed up HR processes; improve communication; reduce the HR headcount; and capture, create and transfer some HR knowledge more accurately and speedily. These advantages can help to increase employee productivity (Foster, 2010;CedarCrestone, 2010CedarCrestone, , 2014Lengnick-Hall and Moritz 2003;Marler and Parry, 2016;Martin, Reddington and Alexander, 2008;Parry, 2011). More broadly, e-HRM, by increasing transparency and clarity over HR policies, may help to improve employee satisfaction with HR and, in turn, lead to greater employee productivity.…”
Section: Impersonal Trust and Employee Productivitymentioning
confidence: 99%
“…In comparison to traditional HRM approaches, e-HRM can help to streamline transactional HRM activities; speed up HR processes; improve communication; reduce the HR headcount; and capture, create and transfer some HR knowledge more accurately and speedily. These advantages can help to increase employee productivity (Foster, 2010;CedarCrestone, 2010CedarCrestone, , 2014Lengnick-Hall and Moritz 2003;Marler and Parry, 2016;Martin, Reddington and Alexander, 2008;Parry, 2011). More broadly, e-HRM, by increasing transparency and clarity over HR policies, may help to improve employee satisfaction with HR and, in turn, lead to greater employee productivity.…”
Section: Impersonal Trust and Employee Productivitymentioning
confidence: 99%
“…Similarly, Ruël et al (2007) suggested the following four goals: cost reduction, improving HR services, improving strategic orientation, and global orientation. However, despite the great potential for HR functions to create value beyond administrative outcomes, in practice, many organizations utilize e-HRM more for an “automating” approach that focuses primarily on administrative efficiency rather than supporting strategic “human capital management” processes (Foster, 2010). According to Foster (2010), while process-based administrative tools are used by more than 90% of organizations, strategic HR technology tools have a much lower organizational penetration rate, typically at the 30% to 40% level (Foster, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Performance links people to work by setting work standards and measures, financial and nonfinancial rewards, and providing feedback in respect of all stakeholder interests (Ulrich & Brochbank, 2005). It is meant to hold employees accountable for their work (Foster, 2010;Knies et al, 2018), recognize those who meet standards while those who fail are sanctioned (Yahiaoui et al, 2015). This provides managers and employees with a clear line of sight between expected behaviours, rewards, and motivation towards optimal service (Ulrich & Brochbank, 2005).…”
Section: Flow Of Performancementioning
confidence: 99%